1996
DOI: 10.1021/jo951910f
|View full text |Cite
|
Sign up to set email alerts
|

Terracinolides A and B, Two Bishomoditerpene Lactones with a Novel Carbon Framework from Euphorbia terracina

Abstract: A methanolic extract of Euphorbia terracina L. has been shown to contain two peracylated polyhydroxy terpenoid lactones with a novel C(22) carbon framework. These metabolites, which have been named terracinolides A (1) and B (2), are based on the same parent compound, but differ in the nature of one of the acyl residues. This novel skeletal system is formally derived from the jatrophane framework by addition of a two-carbon fragment on C-17 (jatrophane numbering).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…ROESY spectra determined the location of a acetate and a isobutyrate at C-2 and C-6, respectively. The relative configuration of terracinolide J (11) was investigated by measurement of scalar and dipolar couplings as well as by comparison with literature data (Appendino et al 1998;Marco et al 1996Marco et al , 1997, and has been found identical to that of all known terracinolides isolated to date.…”
Section: Modified Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 85%
See 2 more Smart Citations
“…ROESY spectra determined the location of a acetate and a isobutyrate at C-2 and C-6, respectively. The relative configuration of terracinolide J (11) was investigated by measurement of scalar and dipolar couplings as well as by comparison with literature data (Appendino et al 1998;Marco et al 1996Marco et al , 1997, and has been found identical to that of all known terracinolides isolated to date.…”
Section: Modified Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 85%
“…Compounds 14-17 and 19-20 were identified as the known terracinolides B, C, F, H, and 13a-OH terracinolide B and G, respectively, previously isolated from E. terracina and E. segetalis (Marco et al 1996(Marco et al , 1997(Marco et al , 1999. Compounds 11-20 are based on a 17-ethyl bis-homojatrophane framework, a skeleton previously found in E. terracina diterpenes (Marco et al 1996), from which it takes the name. Preliminary MS and NMR data of terracinolide J (11) suggested that this compound was a diterpenoid polyester with seven ester carbonyls, four acetates and two isobutyrates.…”
Section: Modified Jatrophane Diterpenes: Euphorbia Dendroidesmentioning
confidence: 95%
See 1 more Smart Citation
“…Phytochemical investigation of E. salicifolia resulted in the isolation of salicinolide ( 13 ), a new bishomojatrophane containing a C‐6–C‐9‐bonded eight‐membered lactone ring as a new structural feature. Structurally similar C 22 diterpenes, based on the 17‐ethyljatrophane skeleton, were isolated from other Euphorbia species ( E. terracina , E. segetalis and E. dendroides )18,54,55 but in these compounds (terracinolides and isoterracinolides) the lactones are formed through C‐5–OH and C‐3–OH, respectively.…”
Section: Isolation Of Diterpenesmentioning
confidence: 98%
“…T [29] x Stellera chamaejasme L. T [67] x Pimelea simplex F. Muell. T [72,78] x alkyldaphnanes, it is limited to acetyl residues, as in terracinolides from Euphorbia terracina L. [91]. From a structural standpoint, the occasional reduction of the 3-ketogroup is also noteworthy, and reminiscent of ingenane derivatives.…”
Section: Alkyldaphnanesmentioning
confidence: 99%